Orthostatic reactions and cognitive dysfunctions in elderly and senile patients with arterial hypertension - Irina V Atyunina (Системные гипертензии, 2019)
Aim. To study the relationship of orthostatic hypotensive reactions (OHR), detected using active (AOT) and passive orthostatic tests (POT) with the state of cognitive functions in patients with arterial hypertension (AH) in older age groups. Materials and methods. 75 patients with hypertension I-III stage were examined (67±5 years). Patients received regular antihypertensive therapy, excluding medication on the day of the study. The study of the OHR was carried out using a 5-minute AOT and 5-minute POT with a minute-by-minute measurement of blood pressure on the shoulder using the oscillometric method and continuous non-invasive measurement of systolic (SBP) and diastolic (DBP) blood pressure in the finger artery by a photocompensation method (Task Force Monitor, CNSystems, Austria). The presence or absence of classical orthostatic hypotension (COH) and initial orthostatic hypotension (IOH) was assessed according to the criteria of the European Society of Cardiology (ESC-2018). The study of cognitive functions was carried out using a brief study of the mental state (Mini-Mental State Examination - MMSE), the clock drawing test and the Münstenberg test. The analysis was performed using Statistica 6.0. Data from sets with normal distribution were compared using student's t-test, Mann-Whitney test was used when comparing data with a distribution different from the normal one. To compare the groups on qualitative characteristics used Fisher's exact test. Results. In 23 (31%) patients, different types of OHR were identified, of them, 9 (12%) had isolated IOH, 14 (19%) had COH, among which 7 patients had a combination of COH+IOH). The revealed COH was neurogenic in all patients. The test result for drawing clocks in patients with OHR was significantly worse compared with patients without OHR (7.5±1.5 vs 8.4±0.8, p0.05; MMSE test: 25.7±2.3 vs 26.9±1.2, p>0.05 respectively). Conclusion. OHR was detected in 31% of patients with AH in older age groups. The most pronounced decrease in cognitive functions was observed in patients with hypertension with COH.